Multi-lobed mesiodens with a palatal talon cusp: a rare case report - Nagaveni,Nayaka Basavanthappa (2010)
Mesiodens is a midline supernumerary tooth commonly seen in the maxillary arch and the talon cusp is a rare dental developmental anomaly seen on the lingual surface of anterior teeth. This paper presents a rare clinical case of development of talon cusp in a mesiodens with multiple lobes, which interfered with both occlusion and appearance of an 11-year-old patient. During clinical interview, the patient reported difficulty on mastication. Clinical and radiographic examination revealed that a supernumerary tooth with completely formed root was causing an occlusal interference. The supernumerary tooth was diagnosed as multi-lobed mesiodens associated with a palatal talon cusp. The treatment plan consisted in the extraction of the supernumerary tooth followed by orthodontic treatment for diastema closure and tooth alignment.